2017
DOI: 10.1136/annrheumdis-2016-211064
|View full text |Cite
|
Sign up to set email alerts
|

Faecal microbiota study reveals specific dysbiosis in spondyloarthritis

Abstract: Our results suggest that distinctive dysbiosis characterise both SpA and RA and evidence a reproducible increase in that appears specific for SpA and a marker of disease activity. This observation is consistent with the known proinflammatory role of this bacteria and its association with IBD. It may provide an explanation for the link that exists between SpA and IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
227
4
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(279 citation statements)
references
References 44 publications
28
227
4
8
Order By: Relevance
“…Dysbiosis leading to an upregulated Th17-driven immune response in a genetically susceptible host is another potential common pathogenic pathway 18. Indeed, a recent study reported a specific dysbiosis in patients with spondylitis and a history of IBD 19. Lifestyle factors such as smoking may also have an important role, especially considering that smoking is a known risk factor for Crohn’s disease while smoking is associated with a lower risk of developing ulcerative colitis 20.…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis leading to an upregulated Th17-driven immune response in a genetically susceptible host is another potential common pathogenic pathway 18. Indeed, a recent study reported a specific dysbiosis in patients with spondylitis and a history of IBD 19. Lifestyle factors such as smoking may also have an important role, especially considering that smoking is a known risk factor for Crohn’s disease while smoking is associated with a lower risk of developing ulcerative colitis 20.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Data on changes in gut microbiota in SpA are emerging, 29 but it remains to be determined whether the microbiome of axSpA patient has a distinct signature and whether and how the microbiome influences disease. In these models, rats and mice develop SpA-like clinical and pathologic features when housed in a regular laboratory environment, but not when raised in a germ-free environment.…”
Section: Infection or Microbiome?mentioning
confidence: 99%
“…A second organism that has emerged in these studies is the Ruminococcaceae family, which was increased in the ERA and in the polyarticular JIA patients in the Di Paola study as well as in the Italian patients in the van Dijkhuizen study . While this was not further speciated, one might speculate as to whether this was Ruminococcus gnavus , which was increased in two cohorts of patients with SpA and correlated with disease activity among those with concomitant inflammatory bowel diseases (IBD) . As with Akkermansia muciniphila , which Stoll et al linked to subjects with ERA, R gnavus has a strong ability to digest intestinal mucins, thus providing one potential mechanism by which the microbiota might predispose to disease.…”
Section: Microbiota Alterations In Jiamentioning
confidence: 99%
“…In contrast, in the world of inflammatory diseases, there are not for the most part “good guys” or “bad guys.” Rather, the impact of a specific organism is likely to depend on the age of exposure, other community members, host genetics, the host's immune response against the organism, and myriads of other factors. Thus, species that emerge as pathogenic in one condition (eg, Prevotella and RA may be reduced in another; pediatric exposure to Bacteroides may predispose to JIA while adult exposure may be protective; and mucin‐degrading organisms such as A muciniphila and Ruminococcus may be harmless in isolation but harmful in the right setting . Furthermore, many of the organisms identified as potentially relevant to JIA pathogenesis may be beneficial for other reasons, and their obliteration even if technically possible may have downstream effects that would need to be monitored.…”
Section: Therapeutic Potential Of Microbial Alterationmentioning
confidence: 99%